Morphometric and connectivity white matter abnormalities in Obsessive Compulsive Disorder - Gonçalves, Óscar F. (2016)
Two psychological mechanisms seem to be associated with the obsessive-compulsive cycle: (1) an emotional mechanism characterized by intense emotional arousal associated with intrusive thoughts of impending danger; (2) a cognitive mechanism exemplified by difficulties with inhibitory control. Several studies found more extensive cognitive deficits in Obsessive Compulsive Disorder (OCD) beyond problems of inhibitory control and emotional regulation, namely: visual-spatial processing and memory. Thus, there is now extensive research showing that alterations of these psychological mechanisms in OCD (i.e., inhibitory control, emotional regulation, working memory, and visual spatial processing) are associated with morphological gray matter alterations in widespread brain regions. More recently, researchers have started looking at white matter abnormalities in OCD. In this article we review the research looking at white matter morphometric and structural connectivity alterations in OCD. Altogether, while some contradictory findings are still present, there is now evidence for widespread white matter morphometric and connectivity abnormalities affecting major white matter tracts (superior longitudinal fasciculus, inferior fronto-occipital fasciculus, inferior longitudinal fasciculus, cingulum bundle, semioval center, internal capsule, different regions of the corpus callosum, thalamic radiation, uncinate fasciculus and optic radiation) as well as white matter in regions adjacent to gray matter structures (superior frontal gyrus, dorsolateral prefrontal medial frontal cortex; inferior frontal gyrus, caudate, insulate cortex, parietal cortex, supramarginal and lingual gyri, and thalamus). These white matter alterations may help explaining the diversity of OCD psychological impairments in inhibitory control, emotional regulation, memory and visual spatial processing.